(untitled) (Academia Science Repository, 2023)
This article discusses the features of the translation of technical texts. The relevance of the article lies in the need to improve the quality of the translation of technical texts through the collection of information about cultural and extra-linguistic factors, the need to improve the quality of translated texts, and the elimination of errors in translation.